New Nanosized V(III), Fe(III), and Ni(II) Complexes Comprising Schiff Base and 2-Amino-4-Methyl Pyrimidine: Synthesis, Properties, and Biological Activity - Maged S. Al-Fakeh; Maha A. Alsikhan; Jawza S. H. Alnawmasi; Abdullah H. Alluhayb; Mona S. Al-Wahibi (International Journal of Biomaterials)
A new synthesis of mixed ligand complexes vanadium(III), iron(III), and nickel(II), [M : L1 : L2], where L1 = Schiff base 2-((E)-((4-(((E)-benzylidene)amino)phenyl)imino)methyl)-naphthalene-1-ol (C24H18N2O) as for L2 = AMPY 2-amino-4-methyl pyrimidine (C5H7N3) were prepared in powder and investigated. Element analysis, molar conductivity, FT-IR, UV-vis, and magnetic susceptibility values have been acquired to describe the generated complexes. The values of vanadium(III), iron(III), and nickel(II) compounds are, respectively, 2.88 BM, 5.96 BM, and 2.92 BM, demonstrating that all compounds conform to the recommended octahedral geometry. Thermal gravimetric analysis (TGA) is used to further assess the complexes and establish the temperature stability and degradation of the metal complexes. The calculations abstracted from XRD patterns propose nanosized complexes (average size 29–50 nm). The microstructures of the samples have also been investigated by scanning electron microscopy (SEM). The disc diffusion method was used to assess and analyze the inhibition of the growth of compounds against harmful bacterial and fungal strains. The prepared complexes were tested against three strains of bacteria, one gram-positive strain (Bacillus subtilis), two gram-negative strains (Escherichia coli and Pseudomonas aeruginosa), and one fungus (Aspergillus fumigatus). The complexes inferred antimicrobial activity against the studied organisms. Specifically, vanadium(III) and nickel(II) are more effective than iron(III), making them promising drugs.